El derecho y la realidad, a propósito de la calificación del concebido - Olavarría Vivian, Juan Alejandro (2014)
In this article, the author wonders whether the provision under section I of the Preliminary Title of the Code of Children and Adolescents, which qualifies a conceived baby as a child and human being, plays a useful role and justifies going beyond the precepts stipulated in the Civil Code of 1984 and the Political Constitutions of 1979 and 1993; legal instruments that not only protect human life as from conception but also affirm the value of human life and grant unborn babies the status of subject of law. He wonders why the Code of Children and Adolescents no longer considers zygotes, embryos, fetuses, and neonate despite being indisputable facts.